Evaluation of GMP Compliance on Cosmetics: Case Study on Cosmetic Industries in Indonesia - Rizka Ayu Kusuma Widjanarko; Yudo Anggoro (AIBPM Publisher, 2021)
The cosmetic industry has been designated as one of the priority sectors, as stated in the Master Plan of National Industry Development 2015-2035. The priority development programs in the cosmetic sector are mastering technology and building international standard manufacturing capabilities. The cosmetic industry's ability to comply with international standards, including good manufacturing practices (GMP), is mandatory, mainly since the ASEAN Harmonized Cosmetics Regulatory Scheme was fully implemented. It has been almost 14 years since the scheme's implementation, and the Indonesian FDA has enforced all stipulations within the scheme framework. This study aims to evaluate the policy impact of GMP compliance on cosmetic industries in Indonesia through a cost-benefit analysis. A qualitative descriptive method is conducted to identify the benefits and the costs of GMP compliance and determine the importance or significance of the benefits and costs components. The result findings showed the more significant cost components include maintenance of building and facilities, quality control, maintenance of equipment, and sanitation and hygiene. In comparison, the weight scores of the benefit components do not differ much, with the benefit of increased product sales being perceived to be the most important.